Compression between microcontinents in the Cathaysian Block during the early Yanshanian: petrogenesis of the Tangquan pluton in Southwest Fujian Province, Southeast China. (5th September 2016) - Zhao, Xilin; Yu, Shengyao; Mao, Jianren; Liu, Kai; Yu, Minggang; Jiang, Yang; Chen, Zhihong; Hou, Kejun; Peng, Yinbiao
Abstract : Southeast China is characterized by widespread Mesozoic igneous rocks, which have drawn a great deal of attention in recent decades because of their tectonic significance and related large‐scale mineralization. Among these igneous rocks, The Tangquan pluton in Southwest Fujian Province is the only adakitic pluton that has been discovered within the Cathaysian Block. It is mainly composed of a central unit of granodiorite with peripheral granodioritic porphyries. Two medium‐grained granodiorite samples have zircon U‐Pb ages of 162.2 ± 2.0 Ma and 163.0 ± 1.4 Ma, indicating intrusion in Middle Jurassic times. Adakite‐like geochemical features of the pluton include high Sr/Y (46.7) and (La/Yb)N (25.5) values, and low Y (12.2 ppm) and Yb (1.04 ppm) abundances. All samples have low εNd(t) values (average −9.49) and high initial 87 Sr/ 86 Sr ratios (average 0.708242). These results suggest that the adakitic rocks were generated by partial melting in thickened crust. The Tangquan pluton probably formed during the extrusion collision of microcontinents within the Cathaysian Block related to subduction of the Pacific Plate, which caused crustal thickening and partial melting of Neoproterozoic crust with arc‐like magmatic characteristics. Because the extrusion collision occurred between microcontinents in an intraplate (Cathaysian Block) setting, the effects of the extrusion collision were not as strongly felt as those involved in the Jiangshan‐Shaoxing Fault along which numerous adakitic rocks were emplaced with related porphyry‐type copper deposits. Copyright © 2016 John Wiley & Sons, Ltd.